SURVEY OF EXTRA PULMONARY TUBERCULOSIS IN D.I. KHAN - Khan, Abdus Salam; Mustafa, Ghulam; Khan, Shamsuddin (Journal of Ayub Medical College Abbottabad, 1990)
A total of 360 biopsy specimens were sent to our clinical laboratory by the surgical department of Distt: Head-quarter Hospital, Dera Ismail Khan during the year 1987-88. Out of these, 107 (29.7%) were non-tumors. Twenty of these (18.7%) were proved to be tubercular. Tuberculosis of the skin (35%) was found to be most common followed by G.I.T (20%) Bones and Joints (20%), lymphnodes (15%) and testis (10%). Mostly young adults and to some extent children were affected. Mostly the patients belonged to city slums were of lower socio-economic class and were living in crowded situation.